The effect of subclinical mastitis on milk transforming growth factor-beta level in Anatolian water buffaloes - Gürler, H; Yarım, GF; Yarım, M; Gökçeoğlu, A; Ümit, F (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aims to evaluate the relationship between transforming growth factor beta (TGF-β) and somatic cell count (SCC) in Anatolian buffalo milk. The study material comprised 80 milk samples obtained from the udder quarter of 40 healthy and 40 subclinical mastitic nonpregnant lactating Anatolian buffaloes. The California mastitis test and somatic cell count were performed on milk samples milked from four mammary lobes of buffaloes to diagnose subclinical mastitis. The milk TGF-β level was measured by bovine-specific enzyme-linked immunosorbent assay kit. The milk TGF-β levels in subclinical mastitic and control groups were 11.7±2.6 (8.0 to 18.3) ng/ml and 4.8±1.3 (2.4 to 7.0) ng/ml. The milk TGF-β level of subclinical mastitic buffaloes was significantly higher than healthy ones (P<0.01). A significant positive correlation was determined between the milk TGF-β level and SCC in subclinical mastitic buffaloes (r2 = .936, P < 0.001). This is the first study to determine the relationship between TGF-β concentrations and SCC in milk obtained from mammary quarters with subclinical mastitis in Anatolian water buffaloes. This study has the potential to contribute to studies on cytokine changes in milk in subclinical mastitis of buffaloes.